Evaluating tenants’ satisfaction with public housing in Lagos, Nigeria - Jiboye, Adesoji David (Journal of Architecture and Urbanism, 2009)
This paper examines tenants’ satisfaction with public housing in Lagos, Nigeria. This was accomplished by assessing the levels of housing satisfaction of the general population and the degrees of satisfaction of tenants living in selected public housing estates within Lagos metropolis. Three (3) major housing components – environment (E), dwelling (D), and management (M), were identified and employed for this study. Six (6), representing 10% of estates, were randomly selected from forty (40) public housing estates in Lagos. Subsequently, questionnaires were administered to 1.022 (10%), of households from the total of 12.323 households in the selected estates of the study area.The data obtained from the survey were analyzed in two stages. First, is the use of descriptive analysis such as frequency tabulation to assess the general levels of tenants’ housing satisfaction, and second, is the use of Satisfaction Indices (RSI) to determine the degree of tenants’ satisfaction with each of the housing components identified for the study. The results of the analysis indicate that the level of tenants’ housing satisfaction varies and is dependent on the environment, dwelling and management interaction systems. It demonstrated that the level of tenants’ satisfaction with the housing environment and dwellings was above average (adequately satisfactory), but their level of satisfaction with the housing management was below average (unsatisfactory).The study shows that users’ inputs and preferences should be strongly considered by planners and public housing agencies when planning and designing public housing projects.Gyventojų pasitenkinimo komunaliniais būstais Lagose (Nigerija) tyrimasSantrauka. Straipsnyje nagrinėjamas ir vertinamas Nigerijos miesto Lagos gyventojų pasitenkinimas municipalinio fondo būstais. Autoriaus tyrimas atskleidė, kad pats būstų ir jų aplinkos įvertinimas yra vidutinio lygmens, jų priežiūros ir tvarkymo lygis yra žemesnis. Nustatyta, kad gyventojų pasitenkinimą lemia ir socialinė bei ekonominė, kultūrinė ir fizinė gerovė. Autorius yra įsitikinęs, kad jo tyrimo išvados ir rekomendacijos bus vertingos būstų statybos ir priežiūros įstaigoms, planuotojams ir architektams, formuluojant naujus ateities būstų projektavimo ir priežiūros reikalavimus.Reikšminiai žodžiai: komunalinis būstas, Lagosas, Nigerija, urbanistinė plėtra, respondentai, gyventojai, federalinė ir municipalinė valdžia.First Published Online: 22 May 2013